2009
DOI: 10.1080/09593330903207194
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological effects of cypermethrin on gill, liver and kidney of fresh water fishClarias gariepinus(Burchell, 1822), and recovery after exposure

Abstract: Gill, liver and kidney of Clarias gariepinus were examined histologically after exposure to sublethal concentrations (10.05, 20.10 and 30.15 microg/L) of cypermethrin for 10 days. Histological recovery was also studied by maintaining the pesticide-exposed fish in a fresh water system for an additional 10 days. Epithelial hypertrophy and hyperplasia, epithelial lifting, oedema, fusion of secondary lamellae, necrosis and desquamation were histopathological changes in the gills of fish exposed to cypermethrin. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 28 publications
6
14
0
Order By: Relevance
“…According to Ayub- Shah et al (1996) cypermethrin with lower dose resulting mild disorganization of hepatic laminae and higher dose produced necrosis of hepatic cells, with pyknotic nuclei and dilatation of sinusoids with highly disrupted hepatic laminae 21 . In addition, the findings from the current histological observation are in accord with diverse earlier studies which indicated that the introduction to cypermethrin and other pesticides led to provoke intensive physiological, biochemical, histological turbulence in different experimental animals as rat [17], mice [21], rabbit [22], cat [23], broiler chicks [24] and fish [25]. The similar results are reported for malathion, endosulphon and other pesticides indicating exposure of these pesticide leading to encourage histological disturbances in experimental animals [26, 27 and 28].…”
Section: Discussionsupporting
confidence: 79%
“…According to Ayub- Shah et al (1996) cypermethrin with lower dose resulting mild disorganization of hepatic laminae and higher dose produced necrosis of hepatic cells, with pyknotic nuclei and dilatation of sinusoids with highly disrupted hepatic laminae 21 . In addition, the findings from the current histological observation are in accord with diverse earlier studies which indicated that the introduction to cypermethrin and other pesticides led to provoke intensive physiological, biochemical, histological turbulence in different experimental animals as rat [17], mice [21], rabbit [22], cat [23], broiler chicks [24] and fish [25]. The similar results are reported for malathion, endosulphon and other pesticides indicating exposure of these pesticide leading to encourage histological disturbances in experimental animals [26, 27 and 28].…”
Section: Discussionsupporting
confidence: 79%
“…According to the damage classification scale of Poleksic and Mitrovic-Tutundzic (1994), the mean values for the HAI are in the range from 21 to 50, with indicate occurrence of moderate to severe liver damage, while values from 51 to 100 correspond to occurrence of severe damage (Table 4). These results, like those reported by Mori et al (2018), suggest that even though the damage may compromise the functioning of the organ, inoculation of A. hydrophila and application of the baths with EOs do not induce irreversible tissue damage, as reported in trials with chemotherapies (Sarkar et al, 2005;Velmurugan et al, 2009). Therefore, in the present study, considering the similarity in the degree of tissue alteration and frequency of occurrence of damage in all the treatments with EOs, the occurrence of this damage may have been associated with the infection with A.…”
Section: Stagesupporting
confidence: 82%
“…These results, like those reported by Mori et al (2018), suggest that even though the damage may compromise the functioning of the organ, inoculation of A . hydrophila and application of the baths with EOs do not induce irreversible tissue damage, as reported in trials with chemotherapies (Sarkar et al, 2005; Velmurugan et al, 2009). Therefore, in the present study, considering the similarity in the degree of tissue alteration and frequency of occurrence of damage in all the treatments with EOs, the occurrence of this damage may have been associated with the infection with A .…”
Section: Discussionmentioning
confidence: 62%
“…Hepatic lesions in the liver tissues were characterized by cloudy swelling of hepatocytes, lipoid vacuoles, pycnotic nuclei and focal necrosis. Necrosis in the epithelial cells and pycnosis in the hematopoietic tissue in kidney tissues of Clarias gariepinus were observed by Velmurugan et al (2009). Larval deformities in Japaneese medaka (Oryzas latipes) due to cypemethrin toxicity were reported by Younghee et al (2008).…”
Section: Histopathological Alterationsmentioning
confidence: 86%